Anthelmintic Activity Ethanol Extract of Ocimum sanctum Linn. Leaves Against Ascaridia galli In Vitro - Vanna Lidya Kharisma; Setiawan Koesdarto; Koesnoto Supriandono; Lucia Tri Suwanti; Sri Agus Sudjarwo; Kusnoto Kusnoto (Universitas Airlangga, 2018)
The aims of this research are to determine concentration, exposure time, interaction between concentration and exposure time of ethanol extract of Ocimum sanctum Linn. Leaves to cause death toward Ascaridia galli in vitro, and the value of LC50 and LC90 ethanol extract of Ocimum sanctum Linn. Leaves. Research design that has been used in the research was completely randomized design. This research used 200 samples of Ascaridia galli with length 7-11 cm without differentiating their sex. The concentration ethanol extract of Ocimum sanctum Linn. leaves were 1.25%, 2.5%, 5%, 10%. The control was using CMC-Na 0.5%. Each treatment then being replicated four times. The observation and recording of dead worm were done at 0, 3, 6, 12 and 24 hours. Ascaridia galli were declared dead if there was no movement while disturbed by anatomy tweezers and dipped in slightly warm water (50ºC). The obtained data was analyzed using Anova Factorial and continued with Duncan Multiple Range Test by SPSS for Windows 22. The result were 10% concentration and exposure time for 24 hours caused the most mortality toward Ascaridia galli. Interaction between concentration and exposure time resulted 10% concentration ethanol extract of Ocimum sanctum Linn. leaves in 24 hours caused the most mortality towards Ascaridia galli. Probit analysis was used to calculate the LC50 and LC90 of Ocimum sanctum Linn. leaves. The results were LC50 ethanol extract of Ocimum sanctum Linn. leaves at 6 hours was 14.8%, at 12 hours was 4.8% and at 24 hours was 3.0% and the LC90 at 24 hours was 9.1%.